Pengembangan Website Sekolah SD-SMP Methodist Romalbest Medan - Riche Riche; Sophya Hadini Marpaung (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
The current community service activity is aimed at solving problems that exist at the Methodist Romalbest Medan School (SD-SMP Methodist Romalbest). By providing an output in the form of a school website that is used by the school to convey information and at the same time as a medium for school promotion. This is important because recently the delivery of information/promotions through the website has been widely carried out by similar agencies and the website is one of the media that is quite easy to use and has a wide reach. The website will be built by first collecting data that will be published on the website and then the content of the website will be adjusted to the request from the Romanbest Methodist school.